2016
DOI: 10.1039/c5tc04041h
|View full text |Cite
|
Sign up to set email alerts
|

The preparation and phase diagrams of (7Li1−xFexOD)FeSe and (Li1−xFexOH)FeSe superconductors

Abstract: We report the phase diagram for the superconducting system (7Li1−xFexOD)FeSe and contrast it with that of (Li1−xFexOH)FeSe both in single crystal and powder forms.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
44
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(52 citation statements)
references
References 50 publications
6
44
2
Order By: Relevance
“…Refinements with PXRD were limited to occupation of total transition metal (M * ) doping in the hydroxide layer as well as total transition metal in the FeSe layer yielding a formula: (Li 1−x M * x OD)M y Se. Rietveld refinements of the powder x-ray diffraction yielded a composition of (Li 0.875(2) M * 0.125(2) OD)M Se with lattice parameters a = 3.8008(1)Å and c = 9.2394(2)Å which is in close agreement with previous works 3,4,11,41 .…”
Section: Hydrothermal Synthesis and Crystallographic Resultssupporting
confidence: 88%
“…Refinements with PXRD were limited to occupation of total transition metal (M * ) doping in the hydroxide layer as well as total transition metal in the FeSe layer yielding a formula: (Li 1−x M * x OD)M y Se. Rietveld refinements of the powder x-ray diffraction yielded a composition of (Li 0.875(2) M * 0.125(2) OD)M Se with lattice parameters a = 3.8008(1)Å and c = 9.2394(2)Å which is in close agreement with previous works 3,4,11,41 .…”
Section: Hydrothermal Synthesis and Crystallographic Resultssupporting
confidence: 88%
“…Therefore, the superconducting samples contains more Fe in the hydroxide layer and consequently more electron doping (0.13 e – vs. 0.09 e – ) into the FeS layer. Similarly, Zhou et al 25 have reported that for the selenide analogues, higher T c 's were achieved with lower reaction temperatures so that more iron cations could incorporate into the lithium hydroxide layer. Studies on the same system by Clarke et al demonstrated that the iron in the hydroxide layer is Fe 2+ and that iron vacancies in the FeSe layer degraded the superconducting properties.…”
Section: Resultsmentioning
confidence: 89%
“…The latter condition was maintained by the inclusion of tin metal plate as a way to dynamically change the hydrothermal conditions from oxidizing to more reducing. 25 No tin was found in the products as determined from energy dispersive X-ray spectroscopy (EDS).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, neutron diffraction study by Zhou et al x Fe x OD)FeSe found crystallographic evidence for O-D· · ··Se bonding where the Se-D distance was approximately 3.03Å. [153] The intercalation chemistry of FeSe also has similarities with the superconducting fullerenes (see section ??). The amount of charge doping in both sets of materials seems to be critical to raising the T c .…”
Section: Discussionmentioning
confidence: 99%